2001
DOI: 10.1088/0953-8984/13/31/202
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In this review, we present various results obtained by friction force microscopy in the last decade. Starting with material-specific contrast, commonly observed in friction force maps, we discuss how the load dependence of friction and the area of contact have been estimated and compared to elasticity theories. The features observed in a sliding process on the atomic scale can be interpreted within the Tomlinson model. An extension of the model, including thermal effects, predicts a smooth velocity dependence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
143
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(155 citation statements)
references
References 111 publications
(119 reference statements)
10
143
1
1
Order By: Relevance
“…Such hysteretic behavior, shown in more detail on Fig. 2(c), can occur spontaneously without any intervention on our part and is reminiscent of atomic friction [23,24]. As it turns out, the hysteretic behavior is very short lived as the nanotube is cycled.…”
mentioning
confidence: 64%
“…Such hysteretic behavior, shown in more detail on Fig. 2(c), can occur spontaneously without any intervention on our part and is reminiscent of atomic friction [23,24]. As it turns out, the hysteretic behavior is very short lived as the nanotube is cycled.…”
mentioning
confidence: 64%
“…[1][2][3] Energy is dissipated by conversion of kinetic energy of the moving bodies into lattice vibrations or phonons ͑heat͒. Even before contact is established, fluctuating electric fields emanating from charges in the two bodies exert forces on each other that produce work ͑dissipation-fluctuation theorem͒.…”
Section: Introductionmentioning
confidence: 99%
“…Atomic force microscopy ͑AFM͒ is particularly suited for this investigation, since it makes possible both the measurement of tribological properties and surface visualization at the nanometer scale. [1][2][3][4] One can thus detect the onset of surface damage-inelastic deformation-with atomic-scale precision. [5][6][7][8] Previous experiments with well characterized surfaces carried out in ultrahigh vacuum ͑UHV͒ have shown that the relation between friction force and contact area can be described by the Derjaguin-Müller-Toporov 3,9 ͑DMT͒ or the Johnson-Kendall-Roberts ͑JKR͒ model, 10,11 depending on the adhesion energy and on the hardness of the contacting materials.…”
Section: Introductionmentioning
confidence: 99%